PROTEIN AND ORGANIC RESIDUE (FTIR) ANALYSES OF SAMPLES FROM SITES HHOV 374, HHOV 506, HHOV 508, HHOV 512, HHOV 513, HHOV 514, HHOV515, HHOV 517, AND HHOV 520, MUSKEG RIVER MINE EXPANSION PROJECT, ALBERTA, CANADA - Yost, Chad (PaleoResearch Institute); Logan, Melissa K. (PaleoResearch Institute) (the Digital Archaeological Record)
A total of 28 lithic artifacts were submitted for protein residue analysis from nine sites in close proximity from northeastern Alberta. In addition, 2 samples of fire broken rock were submitted for organic residue analysis using Fourier Transform Infrared Spectroscopy (FTIR). These artifacts were recovered during archaeological survey work associated with the Muskeg River Mine Expansion Project. The project area is located approximately 60 km north of Fort McMurray. Protein and organic residue analysis are used to identify trace residues of plant and animal material that may be present on the surfaces of these artifacts.